MANAGEMENT CHARACTERISTICS AS DETERMINANTS OF EMPLOYEE CREATIVITY: INTERACTIONAL AND DISTRIBUTIVE JUSTICE ON EMPLOYEE JOB SATISFACTION - Riska Amelya; Unggul Kustiawan (SEAN Institute, 2023)
The discussion in this study discusses the influence of humble leadership, rough supervision, interactional and distributive interactions that affect employee job satisfaction as a factor that mediates the effect of exogenous variables on endogenous variables, namely employee creativity. The purpose- of this study is to determine what factors influence employee creativity and employee job satisfaction. This research was conducted by distributing online questionnaires with purposive sampling of skin care company employees whose tenure was more than one year and this study used the SEM method using SPSS and Lisrel software. The findings- in this study are that all the proposed factors have a positive effect on the vocal variables of this research, although there is a difference with one hypothesis proposed, namely the role of rough supervision on employee job satisfaction.